2015
DOI: 10.1161/circulationaha.114.013478
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiomyopathy in Younger Persons With a Family History of Death from Cardiomyopathy

Abstract: Background— Recommendations for presymptomatic screening of relatives of cardiomyopathy patients are based on findings from tertiary centers. Cardiomyopathy inheritance patterns are fairly well understood, but how cardiomyopathy in younger persons (<50 years) aggregates in families at the population level is unclear. In a nationwide cohort, we examined the risk of cardiomyopathy by family history of premature death (<60 years) from cardiomyopathy. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For some forms of cardiomyopathy, there is evidence of significant dependence on unmeasured environmental exposures and dynamism in the underlying phenotypes. 12 Ranthe et al 11 also emphasize that their results reinforce calls for family-targeted screening in the aftermath of sudden cardiac arrest.…”
Section: Macrae Clinical Context In Genomics 993mentioning
confidence: 80%
“…For some forms of cardiomyopathy, there is evidence of significant dependence on unmeasured environmental exposures and dynamism in the underlying phenotypes. 12 Ranthe et al 11 also emphasize that their results reinforce calls for family-targeted screening in the aftermath of sudden cardiac arrest.…”
Section: Macrae Clinical Context In Genomics 993mentioning
confidence: 80%
“…Screening for disease prior to the onset of symptoms can catch diseases at an early stage, but may not be useful or affordable for an entire population. Screening asymptomatic individuals can be recommended when there is an additional reason to suspect that an individual may develop disease, such as family/breed history of the disease or a genetic test result indicating susceptibility to disease [95,96]. A positive genetic test result often does not fully predict disease development, but merely indicates that the individual has a genetic pre-disposition to developing the disease [139].…”
Section: Discussionmentioning
confidence: 99%
“…A positive genetic test result often does not fully predict disease development, but merely indicates that the individual has a genetic pre-disposition to developing the disease [139]. Thus, a positive genetic test result does not always result in direct medical intervention, yet it can lead to increased awareness of the disease and enrolment of the individual on a health monitoring programme [92,96]. Not only can the dog be an excellent model, but lessons can also be learned from other species with DCM [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether athletes in general have an increased risk of cardiac arrest and thereby whether athletes should be screened for unknown cardiac disease has been highly debated (Holst et al., ; Harmon et al., ). The Danish Society of Cardiology (DCS) has decided not to recommend screening of athletes but to offer all first‐degree relatives to a SCA or SCD family member under the age of 50 years examination for inheritable heart disease, as family history is a much more significant risk factor of cardiac arrest (Ranthe et al., , ). Moreover as it has been shown that many athletes suffering SCD had cardiac symptoms, that were ignored prior to the event, it seemed prudent to offer athletes with cardiac symptoms examination.…”
mentioning
confidence: 99%